(3GdeTcGI GdZQhjI Ydi GddeYI GdOeTbjIs - (3LhGO GdeYQha HedG cJGHs
(3ChdgG (B:s
(3bhdg GdaU GdSGHY ai HjGf CMcGe GdNdd ai GdUdGI s
(3BNQgG (B:s
(3hdh cGf YGdekG Ch MLGekG hdh cGf RGgOkG dhOHGZkG hdhcGf YGHOkkG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis